2019
DOI: 10.5812/aapm.83975
|View full text |Cite
|
Sign up to set email alerts
|

Appendectomy Pain Control by Transversus Abdominis Plane (TAP) Block in Children

Abstract: BackgroundPain control after surgery in children is very important. Despite having good analgesic effects, the use of opioids is, however, limited due to side effects.ObjectivesThis study was aimed to investigate the effect of transverse abdominis plane (TAP) block on the intensity and frequency of pain after appendectomy in children.MethodsIn a single-blinded clinical trial, 40 children aged from 4 to 16 years, candidates for the appendectomy, were divided randomly to intervention and control groups. The inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Except for Jalil et al, 75 comparing different doses of ropivacaine, all studies reported adequate baseline analgesia. All but one 77 showed a statistically and clinically significant pain reduction by use of the TAP block. Ghimire, as well as Patel and colleagues, demonstrated a reduction of pain lasting 12 h postoperatively 72,73 .…”
Section: Regional Analgesia Techniquesmentioning
confidence: 88%
See 2 more Smart Citations
“…Except for Jalil et al, 75 comparing different doses of ropivacaine, all studies reported adequate baseline analgesia. All but one 77 showed a statistically and clinically significant pain reduction by use of the TAP block. Ghimire, as well as Patel and colleagues, demonstrated a reduction of pain lasting 12 h postoperatively 72,73 .…”
Section: Regional Analgesia Techniquesmentioning
confidence: 88%
“…Transverse abdominis plane block Twelve studies (three for laparoscopic appendicectomy in adults, [67][68][69] one for open appendicectomy in adults, 70 one for laparoscopic in children, 71 and seven for open appendicectomy in children) [72][73][74][75][76][77][78] assessed the analgesic effect of transverse abdominis plane (TAP) block. Eleven out of the twelve studies included adequate baseline analgesia.…”
Section: Regional Analgesia Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample size was calculated using the effect size technique (ES), with ES=0.19, α=0.05 and 95% confidence level. 10 Sixty patients were divided into two groups of 30 each using the consecutive sampling technique, with group-A receiving Bupivacaine caudal block and group B receiving Bupivacaine wound infiltration after open herniotomy.…”
Section: Methodsmentioning
confidence: 99%
“…The concentration and the dose of local anesthetics (LA) have particular importance for the success of pain control. Recent data from randomized controlled trials (RCTs) showed improved clinical efficacy of TAPB when using ultrasound (US) compared with other common pain control techniques [ 2 , 6 9 ]. The TAPB is an interfascial plane block; therefore, the success of the block depends on the volume of local anesthetic injected.…”
Section: Introductionmentioning
confidence: 99%